Economic losses caused by fires in years of the fire peak in the most frequently fire-damaged stands in the Kharkiv green belt - Мельник , Є. Є.; Ворон , В. П.; Сидоренко , С. Г.; Коваль , І. М. (Forestry and Forest Melioration, 2023)
Introduction Over the last 20-year period, almost every year, large wildfires have been recorded in Ukraine and many countries around the world. After such fires, it is difficult to calculate all the economic losses, since a significant part of the damaged territory suffers greatly not only direct losses, but also indirect ones (losses from the reduction of anti-erosion, field protection, recreational, health-improving, water protection, and water regulation functions of the forest, etc.). The aim of the study was to determine a structure by types of possible direct economic losses during fire peak periods in Vasyshchevo Forestry, one of the most frequently damaged forest divisions in Kharkiv green belt. Materials and Methods The average annual trends in the occurrence of forest fires were analyzed through the database of fires formed on the data from the Book of Forest Fires of the Zhovtneve State Forest Enterprise, in which Vasyshchevo Forestry is included, for the period from 2002 to 2021. The number and area of fires were estimated and the average actual flammability for the studied forestry was analyzed separately for each year. The loss of wood marketability in the year of damage and its share in the total annual losses were analyzed. In a similar way, the costs of further work on carrying out the necessary sanitation treatments, i.e. felling, as well as funds aimed at the establishment of forest stands and their care by means of maintenance felling, were compared. That is, the expenses for the needs of continuous sanitation treatments and reforestation of fire-damaged areas were analyzed in detail. Results According to our research, the actual yield of commercial wood after surface fires was only 14 to 16%. As a result, after fires and sanitation activities, forest enterprises lost 216 m3 and 210 m3 of commercial wood per hectare, which is 82 % and 83 % of the potential output without damage, respectively. Total losses due to the cost of wood in 2009 reached UAH 636,305; in 2010 they reached UAH 722,876, which is UAH 69,163 per hectare on average for the year 2009 and UAH 47,872 for the year 2010. After damage by fires, significant funds are needed to restore the forest: 3,074 UAH were used per 1 hectare in 2009 and UAH 3,990 in 2010. According to the methodical instructions for all types of thinning, the maintenance costs make on average 5,568 UAH per 1 ha. Conclusions In Scots pine stands damaged by surface fires, the main damage is caused by the loss of wood marketability (56–68%). More than 22% is spent on sanitation treatments with removal and skidding of wood. Costs for reforestation account for only 6–12%. From 5 to 10 % of the funds from the total amount of losses are required for improvement felling. The availability of the above data makes it possible to better assess the negative consequences of fires in the pine forests of the green zone of the city of Kharkiv under the most severe scenario (peaks of flammability) and can help the managers in the enterprise to in time prepare for possible threats and mitigate their consequences in the future. Taking into account the fact that the biggest losses occur due to a loss of marketability, it is necessary to carry out continuous sanitation felling in a timely manner, which should be based on a scientifically sound prediction of tree mortality of damaged pine forests and constant monitoring of areas affected by fires. 2 Figs., 4 Tables, 21 Refs.